إستخدام التمثيلية المسرحية، الدراما في تعليم اللغة العربية للناطقين بغيرها - شهابي، توفيق ياسين أحمد عبد الرحمن (Ma'had al-Tarbiyyah, al-Jami'ah al-Islamiyah al-'Alamiyah fi Maliziya, 2008)
This research work investigates a newly comprehensive method of teaching Arabic to non-Arabic speakers by using dramatization. Despite the theoretical element of dramatization, the study aided to examine the practicality of the practice at the (CELPAD) in International Islamic University, Malaysia. The indispensable purpose of focusing on practical aspect of the perfect rather than its theoretical concept was to examine the success level of dramatization in teaching language, therefore knowing student interests of learning through this method. The findings revealed that experimental group which, learns through dramatization scored higher results compared to control group which, learns by traditional method of learning. Nevertheless, the study provided evidence that student who were used to dramatization in learning process developed considerable interest in learning Arabic Language.